PENGELOLAAN DAYA TARIK PANTAI BERBASIS PEMBERDAYAAN MASYARAKAT (STUDI KASUS PANTAI GESING KABUPATEN GUNUNG KIDUL YOGYAKARTA) - Su harto (Journal of Tourism and Economic, 2018)
The development of the attraction of tourist destinations is synonymous with management. The aim is that destination visited by tourists one of which is the development of attraction. In order to have real implications, the development of tourist attraction must be community-based, this makes sense because by the increase in attractiveness and by the increasing tourist visits it impacts on the economic, social and cultural community.This paper is based on the results of a survey conducted at Gesing Gunung Kidul Beach through exploration and observation methods on Gesing Beach tourist attraction and community involvement in it. Gesing Beach has natural attractions, cultural attractions and special interest tours that require management in order to increase tourist visit, but management is not yet fully based on the potential of the community due to the low level of education and public knowledge about tourism. Community involvement is limited to physical activities such as mutual assistance to repair roads, economic activities such as traditional food stalls. The cultural attractions that exist are only as annual routine activities for the remains of their ancestors. To further empower the community, it is necessary to synergize the three parties, namely the government, the private sector and the community itself, through the establishment of a network of cooperation, counseling, assistance, additional working capital. Addition to managerial insight in the tourism sector and the provision of working capital to fishermen, stall owners, organizations or community tourism groups.Keywords: Management of Tourist Attraction, Community Empowerment, Gesing Beach